Purchase attributes that may influence the use of mineral nucleus for composition of the diet of cattle in confinement (Research, Society and Development, 2021)
This study aims to identify the determinants of the decision to purchase mineral nucleus by breeders of confined beef cattle in the Midwest. For that, a quantitative descriptive research was developed, carried out through the application of structured questionnaires to 83 cattle confiners in the Midwest region of Brazil. After data collection and sample characterization, binary logistic regression and cluster analysis were performed. It was concluded that the data do not allow the prior identification of the influence of the selected purchase attributes (agility of delivery, technical follow-up, brand confidence, guarantee level, indication of the brand by a friend, payment term, product price, brand indication by technician, relationship with the representative and performance result) in the purchase decision and use of mineral cores (whole grains or traditional) in the diet of confined beef cattle. The grouping analysis of specific types of managers obtained answers that are not related, not allowing the distinction between groups. The results open a new point of analysis for purchasing behavior for production: the search for standardization of processes and understanding of the profile of the producer.